MARKETING COMMUNICATION STRATEGIES : ONLINE RETAIL IN PANDEMIC COVID-19 (Qualitative Descriptive Study on Instagram Account @Mlijo.Online.Mjk - Eka Widi Triwulandari; Syaifuddin Zuhri (Universitas Islam Balitar, 2022)
The purpose of this study is to find out how the marketing communication strategy is carried out by @mlijo.online.mjk on Instagram accounts in the midst of the COVID-19 Pandemic. This study uses a qualitative approach with a descriptive method which aims to describe or describe qualitatively the marketing communication strategy carried out by @mlijo.online.mjk on Instagram accounts in the era of the COVID-19 Pandemic. Based on the results of the analysis of the Marketing Communication Strategy on the @mlijo.online.mjk Instagram Account in the Middle of a Pandemic, it can be concluded: From the results of this study indicate that the marketing communication strategy carried out by @mlijo.online.mjk is effective by conducting a SWOT analysis, STP , and the 4P promotion mix (product, price, place, promotion) proved that the Instagram account @mlijo.online.mjk was able to use marketing communication strategies in the midst of a pandemic